(untitled) (Jurnal EurekaMatika, 2020)
As technology advances, secret messages are becoming increasingly vulnerable to hacking. Therefore, the security of these messages must be enhanced. Cryptography studies techniques or algorithms to secure messages, including the Hill cipher and Elliptic Curve Cryptography (ECC). The Hill cipher is a cryptosystem that uses a matrix as its key, with common matrix keys being of a specific size. Elliptic Curve Cryptography utilizes points on an elliptic curve, which is a field over prime numbers, with point addition operations. This research presents the development of a hybrid cryptosystem by combining the Hill cipher and Elliptic Curve Cryptography. In this combination, a modification is performed so that the Hill cipher can utilize a matrix key of size n × n. This integrated cryptography system uses 95 characters from the ASCII set. Furthermore, the research results are implemented into a computer program. The combination of these two cryptosystems aims to improve the security of confidential messages, making them significantly harder to breach. Keywords: Elliptic Curve Cryptography (ECC), Hill Cipher, Modified Hill Cipher. ABSTRAK Seiring perkembangan teknologi, pesan rahasia semakin rentan untuk diretas. Oleh karena itu, pengamanan terhadap pesan rahasia perlu ditingkatkan. Kriptografi mempelajari teknik atau algoritma untuk mengamankan pesan, diantaranya adalah hill cipher dan elliptic curve cryptography (ECC). Hill cipher merupakan suatu kriptosistem yang menggunakan matriks sebagai kuncinya, dengan kunci matriks yang umum digunakan merupakan suatu matriks berukuran. Elliptic curve cryptography menggunakan titik-titik pada kurva eliptik yang merupakan suatu lapangan atas bilangan prima dengan operasi penjumlahan titik. Dalam penelitian ini disajikan pengembangan kriptosistem hill cipher dan elliptic curve cryptography dengan cara menggabungkan kedua kriptosistem tersebut. Dalam penggabungan tersebut, dilakukan suatu modifikasi sehingga hill cipher yang digunakan dapat memiliki suatu kunci matriks yang berukuran Kriptografi gabungan hill cipher dan elliptic curve cryptography ini menggunakan 95 karakter dari bilangan ASCII. Selain itu, hasil penelitian diimplementasikan menjadi suatu program komputer. Penggabungan kedua kriptosistem ini bertujuan untuk meningkatkan keamanan suatu pesan yang bersifat rahasia sehingga pesan tersebut lebih sulit untuk diretas.